Improved Revenue Bounds for Posted-Price and Second-Price Mechanisms - Beyhaghi, Hedyeh; Golrezaei, Negin; Leme, Renato Paes; Pál, Martin; Sivan, Balasubramanian (Operations Research, 2021)
How to optimize posted price mechanisms? The sequential posted-price (SPP) mechanism is one of the widely used selling mechanisms in practice. In this mechanism, the seller presents each buyer with a price sequentially and the buyer can either accept or reject the mechanism's offer. Despite the widespread use of the SPP mechanism, the problem of optimizing prices in this mechanism has not been fully addressed. In a paper entitled, “Improved Revenue Bounds for Posted-Price and Second-Price Mechanisms,” H. Beyhaghi, N. Golrezaei, R. Paes Leme, M. Pal, and B. Sivan construct SPP mechanisms by considering the best of two simple pricing rules: one that imitates the optimal mechanism and the other that posts a uniform price (same price for every buyer). Their simple pricing rules can be easily generalized to the setting with multiple units and yield the first improvement over long-established approximation factors.